1993
DOI: 10.1002/jso.2930530205
|View full text |Cite
|
Sign up to set email alerts
|

Neural cell adhesion molecule (NCAM) and perineural invasion in bile duct cancer

Abstract: Perineural invasion is associated with tumor spreading and an unfavorable prognosis in a variety of cancers. Recently, neural cell adhesion molecule (NCAM) has been reported to be affinitive to neural tissues, which suggests some relationship between NCAM and perineural invasion. This study was designed to elucidate the role of the expression of NCAM on the development of perineural invasion in bile duct cancer. A histopathologic study was performed on 24 patients with bile duct carcinoma who underwent resecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
46
0

Year Published

1995
1995
2013
2013

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(49 citation statements)
references
References 8 publications
(4 reference statements)
3
46
0
Order By: Relevance
“…PNI has been recognized in many series as prevalent pathologic features of colorectal cancer and is reported in up to 33% of these tumors at the time resection (Knudsen et al, 1983;Ueno, 2001). In otherwise PNI rate were much higher in pancreatic cancer (70-100%) and 75-85% in biliary tract cancer (Nagakawa et al, 1993;Seki et al, 1993). It is reported to be crucial route for the local spread of tumour associated with poor prognosis in head and neck, prostate, pancreas and biliary tract cancers (Carter et al, 1983;Ueno, 2001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PNI has been recognized in many series as prevalent pathologic features of colorectal cancer and is reported in up to 33% of these tumors at the time resection (Knudsen et al, 1983;Ueno, 2001). In otherwise PNI rate were much higher in pancreatic cancer (70-100%) and 75-85% in biliary tract cancer (Nagakawa et al, 1993;Seki et al, 1993). It is reported to be crucial route for the local spread of tumour associated with poor prognosis in head and neck, prostate, pancreas and biliary tract cancers (Carter et al, 1983;Ueno, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…It was not dependent only anatomical specificity, but also special ability of the cancer cell to recognize neural tissue easily by secreting the neural cell adhesion molecule (NCAM). They also demonstrated a significant correlation between PNI and lymphatic and venous blood vessels in bile duct cancer and they suggested that PNI of cancer cells occurred not only as result of direct infiltration, but also by invading the lymphatic vessels and veins around the nerves (Seki et al, 1993). However, the perineural space is now usually accepted as an independent route of cancer spread because it is anatomical different the lymphatic canals (Takahashi et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Correlation between N-CAM expression and perineural spread has been confirmed in a variety of human carcinomas. The existence of the polisialiated form of NCAM in Wilms' tumor, neuroblastoma, pituitary tumor, small cell lung cancer, gallbladder and bile duct cancer, squamous cell cancer of head and neck, and prostat cancer results in perineural invasion and agrressive metastatic behaviour with a poor clinical outcome [20][21][22][23][24][25][26][27][28] . As the expression of the polisialiated form of NCAM correlates with tumor growth and invasiveness because of its role in cell disassociation, ıt was considered to be a poor prognostic criterion in pituitary tumors and rhabdomyosarcoma [22,29] .…”
Section: Discussionmentioning
confidence: 99%
“…Perineural invasion is observed frequently in BDC (45), and the perineural space is thought to provide a suitable environment for tumor cell growth and chemotaxis through the release of soluble mitogenetic and chemotactic factors (46). Intriguingly, interaction between BDC cells and peripheral neural tissues may increase AKT phosphorylation levels in a paracrine fashion, and perineural invasion is reported to be closely associated with BDC patient prognosis (45). Therefore, it is possible that modulation of AKT signaling may contribute to the enhanced radiosensitivity of tumor cells invading along the nerve, resulting in an improved prognosis.…”
Section: Discussionmentioning
confidence: 99%